EPIDEMIOLOGY AND MODERN DIAGNOSTICS OF INTESTINAL YERSINIOSIS - Ostonova Gulrukh Sodiqovna (World Scientific Research Journal, 2025)
Abstract: Intestinal yersiniosis is a widespread acute infectious disease across the globe. Annually, around 3,000–5,000 cases of intestinal infection are registered in our country, with the incidence among preschool-aged children being 3–4 times higher than in adults. A sharp increase in cases occurs during the cold seasons, most often in spring and autumn. In many regions of our country, cases of yersiniosis are not registered due to the complexity of diagnosis, but in some areas, an uneven distribution of the infection is observed.